APLIKASI PEMUPUKAN NPK DAN KORELASINYA TERHADAP PRODUKSI TANDAN BUAH SEGAR KELAPA SAWIT - Rossy Mirasari; Muhammad Ripa'i; Roby Roby (JURNAL AGRIMENT, 2022)
This research is motivated by the needs of oil palm plants whose growth and development depend on the availability of nutrients. So that the fertilization must be done correctly in order to encourage healthy plant growth and maximum FFB production. The purpose of this study was to determine whether the implementation of fertilization was in accordance with the directions and recommendations from the company, and to determine the level of correlation between fertilization and the production of fresh fruit bunches of oil palm. The data collection method in this study was direct observation in the field and then comparing the data obtained in the field with data from the company, and also analyzing the correlation between fertilization and fresh fruit bunches (FFB) production. From the results of observations regarding the right dosage and the right method of fertilizer. The rules for the right dosage and the right method are good because they get an average value of the right dose with a percentage of 89.29%, and the rules for the right method with a percentage of 93.57%. Observations regarding the correlation between fertilization and FFB production obtained a value of 0.994, which means that there is a significant correlation with a very strong and positive correlation coefficient.